(untitled) (Journal of the College of Basic Education, 2023)
Filamentous fungi have been widely used to produce hydrolytic enzymes for many applications. Fungal enzymes amylase were produced using eight Aspergillus niger isolates from eight soil sample in Iraq, were screened for amylase production. A. niger FA6 (isolated from AL-Nasiriya soil) gave maximum amylase yield, The effect of varying pH, temperature, incubation period, carbon sources and_ nitrogen sources of the medium for the productivity of amylase from A.nigerFA6 was _ investigated. The maximum activity of amylase was recorded after 7 days of submerged fermentation at pH 5 and temperature 30°C. from different nitrogen and carbon sources used peptone and sucrose respectively gave maximum amylase yield.